Rattus callitrichus - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Rattus callitrichus (Jentink, 1878). Notes Leyden Mus., p. 12. TYPE LOCALITY: Indonesia, N. Sulawesi, Menado. DISTRIBUTION: Sulawesi. COMMENT: Includes maculipilis, jentinki, and microbullatus; see Musser, 1970, Am. Mus. Novit., 2440:31. Ellerman, 1954, in Laurie and Hill, p. 119, included microbullatus in Paruromys; but see Musser, 1970, Am. Mus. Novit., 2440:31. ISIS NUMBER: 5301410011058021001 as R. callitrichus. 5301410011058065001 as R. maculipilis. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 5), pp. 504-560 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 548, DOI: 10.5281/zenodo.7353037